TWO NEW SCIENTOMETRIC INDICES FOR MEASUREMENT OF COLLABORATION ACTIVITIES OF DEPARTMENTS AND THEIR RESEARCHERS IN ACADEMIC INSTITUTIONS - Mohammadhassanzadeh, Hafez; Samadikuchaksaraei, Ali; Saemi, Nazanin; Salimi Asl, Mohammad (Malaysian Journal of Library and Information Science, 2011)
In general, scientific collaboration represents the quality of research work of co-researchers and the related research institutes. Knowledge exchange is known as one of the principle methods of spreading the science. Lack of collaboration leads to research institutional isolation and prevents science expansion. The previous indices that have been proposed for measurement of the degree of scientific collaboration do not base their assessment on the context of the main goal of the research groups and their scientists. As a scientist’s maximum achievement will happen when he/she work as part of a team with a defined goal, and a team succeeds when it focuses on a defined subject, only the collaborations that are formed for promotion of the goals of the team would be considered constructive. Here, we propose two new indices entitled “collaboration h-index” and “collaborative researchers h-index”, to assess the extent of collaboration activities focused on the main goals of a research team